2017
DOI: 10.1111/jocn.13928
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between swinging and playing of white noise among colicky babies: A paired randomised controlled trial

Abstract: Playing of white noise may be helpful for parents and healthcare personnel in reducing the gas pains of babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…12 Previous studies reported the utilisation of pulling legs toward the abdomen 9,21,23 and positioning the baby. 22 Sezici and Yiğit 24 found that rocking babies reduced their duration of crying. In our study, 7% of the mothers used swaddling, and 38.9% of those who did so stated that it reduced the symptoms of colic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Previous studies reported the utilisation of pulling legs toward the abdomen 9,21,23 and positioning the baby. 22 Sezici and Yiğit 24 found that rocking babies reduced their duration of crying. In our study, 7% of the mothers used swaddling, and 38.9% of those who did so stated that it reduced the symptoms of colic.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also determined that getting a baby with colic to listen to white noise decreased durations of crying. 24,25 The study by Demirel et al 22 determined that mothers preferred getting the baby to listen to white noise and machine noises in similar rates with the purpose of reducing infantile colic. Moreover, McRury and Zolotor 27 found videotaped instruction of behavioural interventions (swaddling, face down or side position, playing white noise, giving a pacifier or breastfeeding) to be ineffective in reducing crying among new-borns.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, participants were recruited from three large public health centres in Kutahya, Turkey 1. Sixty-nine infants were randomised to either receive swinging for 1 week followed by white noise the following week, or the reverse.…”
Section: Methodsmentioning
confidence: 99%
“…Запись звуков дождя громкостью 40-50 дБ, соответствующих частотам белого шума, проигрывалась во время сна. У детей с коликами фоновое воспроизведение белого шума показало лучшие результаты, чем укачивание, в снижении длительности плача и увеличении длительности сна [17].…”
Section: белый шумunclassified